The Fusion of Technology and Tradition: Development Comics on Singhasari’s History - Amalina, Sharfina Nur; Azharotunnafi, Azharotunnafi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Globalization has a significant impact on changes in global values that can marginalize local values that are rich in wisdom. This can have implications for the weakening of one's national identity. Efforts to increase public awareness can be through learning History by making digital comic development products of Singhasari culture. The development aims to produce digital comics of local history based on Singhasari cultural heritage for History learning of MA class X students. Research and Development method of ADDIE model is applied in this research. The results showed that: 1) The analysis stage identifies the need for contextual and interesting digital-based learning media and the gap in students' understanding of local history material 2) The design stage produces storyboards, characters and visual content tailored to learning the history and cultural heritage of Raja Singhasari 3) The Development stage involves validation from material and media experts. The media expert test obtained a score of 86 and the material expert test obtained a score of 85 which indicated that the product was suitable for implementation 4) The implementation stage of 30 class X students obtained a percentage of 88.33 which showed a positive response to the aspects of content, appearance and usefulness of digital commils as learning media. 5) The Evaluation Stage provides user feedback based on the results of the digital comic trial which results in the feasibility of the product being used as a History learning media in class X at the SMA / MA level. Recommendations and follow-up to this research are to conduct experiments aimed at testing the effectiveness of the product